MODEL EVALUASI PENDIDIKAN BERBASIS PROSES MENURUT HADITS - Zainab, Nurul (Pascasarjana UIN ANTASARI Banjarmasin, 2018)
Hadith is the second source of knowledge for Muslims after the Qur'an. The proclamation of a hadith needs to be extracted, to provide power for the development of science because it really comes from the words, actions and taqrir of Prophet Muhammad SAW. In the context of education, there are many hadiths that can serve as the basis of developing the subject of educational evaluation. Based on the study of hadith contained in this article, it is found a hadith history at-Tirmidhi which explains the virtue of honesty and get away from the nature of lies. In addition to the results of research, sanad and matan hadith, this hadith is sahih because the aspect of the content of the hadith does not conflict with the Qur'an and other sahih hadiths. In this article it is also found the meaning of hadith and its implications for the development of educational evaluation that can provide treasures for educators in carrying out the assessment process in learning.Hadis merupakan sumber pengetahuan kedua bagi umat muslim setelah al-Qur?an, kehujjahan sebuah hadis perlu digali sehingga memberikan kekuatan bagi pengembangan ilmu pengetahuan karena memang benar-benar berasal dari ucapan, tindakan maupun taqrir Nabi Muhammad SAW. Dalam konteks pendidikan khususnya evaluasi banyak hadis yang dijadikan sumber landasan pengembangan evaluasi. Berdasarkan penelitian hadis yang ada di dalam artikel ini, didapati sebuah hadis riwayat at-Tirmidzi yang menjelaskan keutamaan kejujuran dan menjauhi sifat kebohongan. Hadits ini bernilai shohih karena secara jalur sanad tidak ada yang terputus dan dari aspek isi hadits tidak bertentangan dengan al-Qur?an dan hadits-hadits shohih lainnya. Selain hasil penelitian sanad dan matan hadits. Di dalam artikel ini juga didapati makna hadis serta implikasinya terhadap pengembangan evaluasi pendidikan yang dapat memberikan khazanah bagi pendidik dalam melaksanakan proses penilaian dalam pembelajaran.